Posted by eric on .
Given f(x)= 4x^2=9x+2 and g(x)=3x2, find and simplify the following:
(f+g)(x)
(fg)(x)
(fg)(3)
I have a few other problems i need help with too so if you want to lend me a hand let me know.

Graphing polynomial functions 
bobpursley,
We will be happy to critique your thinking.

Graphing polynomial functions 
Reiny,
the standard definition of
(f+g)(x) = f(x) + g(x)
so for your functions
(f+g)(x) = (4x^2+9x+2) + (3x2)
simplify this and then
follow the same technique for the other two questions, and let me know what you got